Investigating the relationship between Operational Logistics Service Quality (OLSQ) and customer loyalty: Critical review - Al Nasrie Weli; Sidah Idris; Abdul Rahman Yaakob (Penerbit UMS, 2019)
Logistics service quality (LSQ) is an essential component of operational achievement. Service quality is viewed based on the customer’s evaluation and perception of the logistics service. A good distribution system is required to ensure that product or service can reach customers at the right time and destination. This can attract customers to become loyal to the service provided. Gaining customer loyalty is no doubt amongst the most prioritized concern for the firms. This paper, therefore, will explore previous studies on the relationship between operational logistics service quality (OLSQ) and customer loyalty. This paper uses secondary data to investigate the relationship between OLSQ and customer loyalty. The result of this study is expected to contribute to the existing theories as well as providing knowledge and information to the practitioners in the logistics industry. The critical review suggests that there is a significant relationship between OLSQ and customer loyalty.